Evaluation and validation of suitable reference genes for quantitative real-time PCR analysis in lotus (Nelumbo nucifera Gaertn.) - Wang, Bin; Zhu, Fenglin; Zheng, Xingwen; Yang, Liangbo; Diao, Ying; Hu, Zhongli (Scientific reports, 2024)
The qRT-PCR technique has been regarded as an important tool for assessing gene expression diversity. Selection of appropriate reference genes is essential for validating deviation and obtaining reliable and accurate results. Lotus ( Nelumbo nucifera Gaertn) is a common aquatic plant with important aesthetic, commercial, and cultural values. Twelve candidate genes, which are typically used as reference genes for qRT-PCR in other plants, were selected for this study. These candidate reference genes were cloned with, specific primers designed based on published sequences. In particular, the expression level of each gene was examined in different tissues and growth stages of Lotus. Notably, the expression stability of these candidate genes was assessed using the software programs geNorm and NormFinder. As a result, the most efficient reference genes for rootstock expansion were TBP and UBQ. In addition, TBP and EF-1α were the most efficient reference genes in various floral tissues, while ACT and GAPDH were the most stable genes at all developmental stages of the seed. CYP and GAPDH were the best reference genes at different stages of leaf development, but TUA was the least stable. Meanwhile, the gene expression profile of NnEXPA was analyzed to confirm the validity of the findings. It was concluded that, TBP and GAPDH were identified as the best reference genes. The results of this study may help researchers to select appropriate reference genes and thus obtain credible results for further quantitative RT-qPCR gene expression analyses in Lotus.